2021
DOI: 10.3390/biology10060452
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Lrp4 in Schwann Cells Promotes Peripheral Nerve Regeneration in Mice

Abstract: Low-density lipoprotein receptor-related protein 4 (Lrp4) is a critical protein involved in the Agrin-Lrp4-MuSK signaling pathway that drives the clustering of acetylcholine receptors (AChRs) at the neuromuscular junction (NMJ). Many studies have shown that Lrp4 also functions in kidney development, bone formation, nervous system development, etc. However, whether Lrp4 participates in nerve regeneration in mammals remains unknown. Herein, we show that Lrp4 is expressed in SCs and that conditional knockout (cKO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Krox20 has been identified as the main regulator of SC myelination during the pro-myelination phase, and plays a key role in interacting with Sox10 during the formation of nodes of Ranvier. Krox20 also acts as a transcription factor for the production of MPZ [37; 53; 54], thus emphasizing Krox20’s importance in myelination of axons [39; 55; 56].…”
Section: Discussionmentioning
confidence: 99%
“…Krox20 has been identified as the main regulator of SC myelination during the pro-myelination phase, and plays a key role in interacting with Sox10 during the formation of nodes of Ranvier. Krox20 also acts as a transcription factor for the production of MPZ [37; 53; 54], thus emphasizing Krox20’s importance in myelination of axons [39; 55; 56].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence revealed that Lrp4 expressed in SCs may be crucial for the regeneration of axons via an extrinsic mechanism (190). Moreover, Krox20 is downregulated in Lrp4 conditional gene-deleted mice together with low levels of MPZ (9). In this study, mutant mice exhibited superior repair properties and benefitted from the rapid clearance of myelin and proliferation of SCs that resulted from Krox20 downregulation after injury.…”
Section: Low-density Lipoprotein Receptor-related Proteinmentioning
confidence: 61%
“…Demyelination of injured peripheral nerves typically takes place via Wallerian degeneration (WD) that both negatively regulates myelination and leads to myelin degradation. Reduced expression of myelin-associated proteins may also contribute to rapid demyelination, as this response promotes SC proliferation, clearance of myelin debris, and nerve regeneration (9). We will thus review this process as the first step of the clearance program, as this approach can help us to understand the molecular mechanisms that promote the clearance of myelin sheath fragments (Figure 2).…”
Section: Negative Regulation Of Myelinationmentioning
confidence: 99%
“…Krox20 has been identified as the main regulator of SC myelination during the pro-myelination phase, and plays a key role in interacting with Sox10 during the formation of nodes of Ranvier. Krox20 also acts as a transcription factor for the production of MPZ, 35 , 53 , 54 thus emphasizing Krox20’s importance in myelination of axons. 37 , 55 , 56 …”
Section: Discussionmentioning
confidence: 99%